Organic Agriculture: Farmers Perception and Adaptation in Northern Thailand - Jiumpanyarach, Waripas (Asian Journal of Agriculture and Rural Development, 2021)
This study aimed to examine factors impacting on farmers’ decision to convert from conventional to organic agriculture in Phayao and Nan Provinces, Thailand. The perceptions in conversion from conventional agriculture to organic agriculture toward the intention to change behavior, attitudes, and decision-making were analyzed. The data were collected by questionnaires administered to 124 farmers. The theory of planned behavior and the impacting factors of farm practices using logit model were used for analysis. The reasons for adopting organic agriculture were separated into three categories: (1) knowledge and understanding; farmers understood healthy farming but had little organic farm management information; (2) farm size impacts the costs of production; and (3) farm economics, including costs of delivery, storage, and markets, were a barrier to organic farming. These influenced attitudes, group norms, and perceived behavior. The study found that 50% of farmers using conventional practices were unwilling to change their practices, 16.1% had not decided, but 25.8% decided to change to organic practices. Organic agriculture in the study area increased to approximately 30.65%. The study suggests that farmers’ long-term benefits were implementation of agricultural policies supporting equipment, financial resources, knowledge, green technologies, training, and extension.